The Influence of Parenting and Food Consumption Patterns on the Selection and Consumption of Healthy Food in Early Childhood - Agus Salim; Arifin Mado (Perkumpulan Pengelola Jurnal (PPJ) PAUD Indonesia, 2025)
This study aims to analyze the influence of parenting styles and food consumption patterns on the selection and eating habits of healthy food in early childhood. The research approach uses a quantitative method with a correlational survey design. Data were collected through questionnaires distributed to 139 respondents selected using a purposive sampling technique, consisting of parents of early childhood children from various educational institutions. Data analysis was conducted using Pearson’s correlation statistical tests to measure the relationship between parenting styles (authoritative, authoritarian, and permissive) and food consumption patterns with children’s eating habits. The results indicate a significant positive relationship between authoritative parenting and healthy eating habits in children. Conversely, permissive parenting has a negative correlation with healthy food choices, while authoritarian parenting shows a weak correlation. These findings emphasize the crucial role of parents as behavioral models in shaping children’s eating habits from an early age. Therefore, educational interventions and nutritional counseling for parents are necessary to raise awareness and foster parenting practices that support healthy eating habits in early childhood.